2014
DOI: 10.1371/journal.ppat.1003928
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Exploits Asparagine to Assimilate Nitrogen and Resist Acid Stress during Infection

Abstract: Mycobacterium tuberculosis is an intracellular pathogen. Within macrophages, M. tuberculosis thrives in a specialized membrane-bound vacuole, the phagosome, whose pH is slightly acidic, and where access to nutrients is limited. Understanding how the bacillus extracts and incorporates nutrients from its host may help develop novel strategies to combat tuberculosis. Here we show that M. tuberculosis employs the asparagine transporter AnsP2 and the secreted asparaginase AnsA to assimilate nitrogen and resist acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 67 publications
(88 reference statements)
5
128
0
Order By: Relevance
“…Subverting nutritional restrictions by the host (9, 35) via an autarkic metabolic lifestyle is likely an evolutionary advantage that contributes greatly to Mtb's unmatched persistence in humans. It turns out that this important feature of Mtb's metabolism also is a substantial vulnerability, because several auxotrophic strains of Mtb show significant levels of attenuation in mice (8,16,17,26,(36)(37)(38)(39)(40)(41)(42). However, most of these auxotrophies are less bactericidal than Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subverting nutritional restrictions by the host (9, 35) via an autarkic metabolic lifestyle is likely an evolutionary advantage that contributes greatly to Mtb's unmatched persistence in humans. It turns out that this important feature of Mtb's metabolism also is a substantial vulnerability, because several auxotrophic strains of Mtb show significant levels of attenuation in mice (8,16,17,26,(36)(37)(38)(39)(40)(41)(42). However, most of these auxotrophies are less bactericidal than Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there have been wide-ranging suggestions about its actual function. Recently, it was reported that M. tuberculosis secretes an asparaginase, AnsA, to hydrolyze asparagine and generate ammonium ions, which can then block phagosomal acidification (62). This protein was shown to partially depend on the ESX-5 secretion system for export.…”
Section: Discussionmentioning
confidence: 99%
“…S. Typhimurium is a facultative intracellular pathogen that thrives inside phagocytes, where access to nutrients is limited. To determine if S. Typhimurium, like Mycobacterium tuberculosis (20) and Francisella tularensis (21), catabolizes asparagine to survive and replicate inside phagocytes, we infected bone marrow-derived macrophages cultured from 129X1/SvJ mice with wild-type S. Typhimurium, the ⌬STM1294 single mutant, the ⌬STM3106 single mutant, or the ⌬STM1294 ⌬STM3106 double mutant. After 18 h of infection, we recovered intracellular bacteria and found reduced numbers of the ⌬STM1294 mutant and the ⌬STM1294 ⌬STM3106 mutant relative to the level of the wild-type S. Typhimurium, while the ⌬STM3106 mutant followed the same trend ( Fig.…”
Section: Stm3997 Is Required For S Typhimurium To Cause Inhibition Omentioning
confidence: 99%